Investigation of GNSS integrity augmentation synergies with unmanned aircraft sense-and-avoid systems - Sabatini, Roberto; Moore, Terry; Hill, Chris; Ramasamy, Subramanian (2015)
Global Navigation Satellite Systems (GNSS) can support the development of low-cost and high performance navigation and guidance architectures for Unmanned Aircraft Systems (UAS) and, in conjunction with suitable data link technologies, the provision of Automated Dependent Surveillance (ADS) functionalities for cooperative Sense-and-Avoid (SAA). In non-cooperative SAA, the adoption of GNSS can also provide the key positioning and, in some cases, attitude data (using multiple antennas) required for automated collision avoidance. A key limitation of GNSS for both cooperative (ADS) and non-cooperative applications is represented by the achievable levels of integrity. Therefore, an Avionics Based Integrity Augmentation (ABIA) solution is proposed to support the development of an Integrity-Augmented SAA (IAS) architecture suitable for both cooperative and non-cooperative scenarios. The performances of this IAS architecture were investigated in representative simulation case studies by testing the ability of the SAA system to exploit the predictive (caution) and reactive (warning) integrity flags generated by ABIA. Additionally, the ABIA False Alarm Rate (FAR) and Detection Probability (DP) performances were examined and an initial evaluation of the complementarity with Space-Based and Ground-Based Augmentation Systems (SBAS/GBAS) was accomplished. Simulation results show that the proposed IAS architecture is capable of performing high-integrity conflict detection and resolution when GNSS is used as the primary source of navigation data and there is a clear synergy with state-of-the art SBAS/GBAS in all applicable flight phases.